Overlying Rock Activity Laws and Influential Ranges of Coal Seam Mining in Stubble Areas. (16th April 2022) - Jia, Baoxin; Chen, Hao; Li, Zhiyong; Tang, Zhi
Abstract : This report applies theoretical analysis, similar material simulations, and numerical simulation methods to study the overburden strata movements and influential range of coal mining under pressure stubble conditions and to elucidate the relationship between adjacent coal seams. The pressure, failure, caving, stress, and displacement of crop conditions during coal seam mining were evaluated. The results show that the overlying W9-10 coal face and underlying J16-17 roof experience a long first pressure step, i.e., close to the periodic weighting distance. The working face of the W9-10 coal seam is located in the bending subsidence zone of the working face of the J16-17 coal seam. With the advance of the working face of the J16-17 coal seam, the development and range of overburden fracture of the W9-10 coal seam gradually increase. The supporting pressure and displacement caused by the mining process at the W coal seam have no impact on the coal seam of the stubble area, whereas the mining of the J coal seam leads to a continuous increase in the overburden displacement of the W coal seam; the latter also induces a shift in the maximum displacement to the rear, which is more significant for the stress concentration at the middle and front regions of the stubble area, thus presenting a superposition effect. The stress caused by mining at the coal seam decreases with increasing vertical distance from the roof or floor. For distant coal seams, the main contributing factor is the effect of vertical stress. The influential range of the vertical stress caused by mining in the overlying working face remains within 90 m, whereas the influential range of the stress caused by mining in the underlying working face is relatively large, i.e., it still affects the roadway at distances up to 160 m. The results and discussion presented herein provide significant practical value in terms of understanding the overburden strata activity and its influential range in adjacent mines' stubble areas, which can be used to guide group mining efforts.